Jaringan Sosial Dan Mobiliti Pekerjaan Dalam Kalangan Wanita Indonesia: Kajian Kes Di Pulau Pinang - Radzi, Zurina Mohd (2013)
This thesis aims to identify the forms of social networking that contribute to the economic development of Indonesian women in the informal sectors in Penang. The essence of social networking is about relationship in social agencies that involves the role of individuals with others. Social capital refers to informal norms, value, trust and cooperation that promotes assistance, moral support, security, sources of information and more. Based on social networks and social capital approaches, this thesis aims to explain that the expansion of economic activities among the Indonesians is related to their social networks. Notwistanding the importance of the economic factors in the lives of migrants, this thesis established that the economic enterprises of migrants is facilitated by social factors. In line with the social perspective, the three main objectives of the study are to identify the forms of social networks that assist Indonesian women to get jobs; second objective is to identify the strategies carried out by the Indonesian women in the process of expanding economic activity and the last objective is to examine the role of social networks in the formation of economic niches among the Indonesian women. The study is ethnographic exploration in nature and uses intensive interviewing and participant as observer methods carried out on 30 informants who work in the informal sectors. Informants were selected based on purposive sampling and snow-ball method. The informants’ selection criteria were based on their presence in Malaysia longer than five years and changed jobs at least once. Data collection was carried out from August 2010 to December 2011. This study shows that job mobility of Indonesian women is driven by two important factors which are friendship and marriage.